Praveen won Maybank-ICMS Competition - Norhidayah, Mohamad (2018)
Kuala Lumpur, 20 January – Undergraduates student from Faculty of Chemical & Natural Resources Engineering, Praveen A/L Manogaran won the Maybank-ICMS: Decode. Disrupt. Define Competition. The competition is jointly organized by Maybank Banking Berhad and The International Council of Malaysian Scholars and Associates (ICMS) and was held at Maybank Tower, Kuala Lumpur recently.